Developing an Anti-Xa-Based Anticoagulation Protocol for Patients with Percutaneous Ventricular Assist Devices. Issue 5 (September 2015) - Sieg, Adam; Mardis, B. Andrew; Mardis, Caitlin R.; Huber, Michelle R.; New, James P.; Meadows, Holly B.; Cook, Jennifer L.; Toole, J. Matthew; Uber, Walter E.
<x xml:space="preserve">Abstract</x> Because of the complexities associated with anticoagulation in temporary percutaneous ventricular assist device (pVAD) recipients, a lack of standardization exists in their management. This retrospective analysis evaluates current anticoagulation practices at a single center with the aim of identifying an optimal anticoagulation strategy and protocol. Patients were divided into two cohorts based on pVAD implanted (CentriMag (Thoratec; Pleasanton, CA) / TandemHeart (CardiacAssist; Pittsburgh, PA) or Impella (Abiomed, Danvers, MA)), with each group individually analyzed for bleeding and thrombotic complications. Patients in the CentriMag/TandemHeart cohort were subdivided based on the anticoagulation monitoring strategy (activated partial thromboplastin time (aPTT) or antifactor Xa unfractionated heparin (anti-Xa) values). In the CentriMag/TandemHeart cohort, there were five patients with anticoagulation titrated based on anti-Xa values; one patient developed a device thrombosis and a major bleed, whereas another patient experienced major bleeding. Eight patients received an Impella pVAD. Seven total major bleeds in three patients and no thrombotic events were detected. Based on distinct differences between the devices, anti-Xa values, and outcomes, two protocols were created to guide anticoagulation adjustments. However, anticoagulation in patients who require pVAD support is complex with constantly evolving anticoagulation goals. The ideal level of anticoagulation should be individually determined using several coagulation laboratory parameters in concert with hemodynamic changes in the patient's clinical status, the device, and the device cannulation.